A Literature Review on Domestic Violence Expressed from Gender Perspective - Suzan Naji Sabri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This article provides a review of the literature on domestic violence from a gender perspective. Based on scientific evidence, the main topic of discussion is the gender-related risk factors for intimate partner violence. In order to reveal the role of gender in intimate partner violence, the work examined intimate partner violence through literature sources. Previous research has shown that women, in particular, are more likely than men to become victims of intimate partner violence. One risk factor for this is the reality of being financially dependent, which allows perpetrators to use violence against female partners. Aside from financial issues, other risk factors include pregnancy, a poor communication style between partners, and divorce.